Modification of the existing maximum residue levels for fosetyl‐Al in tree nuts, pome fruit, peach and potato. (8th February 2018) - ,; Brancato, Alba; Brocca, Daniela; De Lentdecker, Chloe; Erdos, Zoltan; Ferreira, Lucien; Greco, Luna; Jarrah, Samira; Kardassi, Dimitra; Leuschner, Renata; Lythgo, Christopher; Medina, Paula; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicants Bayer CropScience Europe and Oxon Italia S.p.A. submitted requests to the competent national authority in Spain and Italy, respectively, to modify the existing maximum residue levels (MRLs) for fosetyl in peach and potato from the intended southern Europe (SEU) uses of fosetyl‐Al. The applicants Adama Agriculture B.V., Fitosanitarios Bajo Riesgo AIE and Almond Board of California submitted each an application to the competent national authority in France to modify the MRLs for fosetyl‐Al in pome fruits, peaches and tree nuts (except coconut) for the intended/authorised uses of the active substance potassium phosphonates. The data submitted in support of the requests were found to be sufficient to derive MRL proposals for all the crops under consideration. Adequate analytical methods for enforcement are available to control the residues of fosetyl‐Al and phosphonic acid in plant matrices under consideration. EFSA concluded that the proposed use of fosetyl‐Al on potatoes and the proposed uses of potassium phosphonates on pome fruits and peaches and the authorised use of potassium phosphonates on tree nuts in the United States are unlikely to result in a consumer exposure exceeding the toxicological reference values for phosphonic acid and fosetyl and therefore are unlikely to pose a risk to consumers' health. However, the risk assessment is considered to be tentative and has to be updated as soon as the approval of the renewal of fosetyl and the review of existing uses of potassium phosphonates and disodium phosphonate is finalised.